A comparison of safety procedures in maintenance management of infrastructures for public and private universities / Syafawati Ruslan - Ruslan, Syafawati (Faculty of Architecture, Planning and Surveying, 2013)
This research is made of in order to fulfill the objectives of the academic project that is executed by all Semester 6 of Bachelor in Building Surveying (Hons) to complete the education series where on the last semester, the author need to do some research with selected topic. Safety Procedures are really important to ensure the maintenance of infrastructures is in good safety environment. Safety procedures is very important to be established to the management of infrastructures in order to ensure all the aspects of safety is being considered to identify the impact of using the safety procedures to the maintenance of infrastructures. There are many procedures have been listed out from starting the works until the end. Safety procedures may be the rules that must be obey by all parties involved in order to keep the workplace is safe and not caused to injury and accidents.A safety procedure is part of the maintenance management that should be concerned by the management. Maintenance management is really important to the infrastructures management. Each of the infrastructures will have their own life span. All the items will deteriorate due to ageing factors. To avoid these to become worse, it should be maintained with the effective system and safety procedures are really needed in these case to ensure the maintenance work has fully obey with safety aspects. There are many infrastructures provided in the educational institution to give comfort and facilities to all of the users. So, it is really important to have the effective maintenance management and safety procedures to ensure the condition of the infrastructures and safety of the users, workers and staffs is being care.